2005
DOI: 10.1002/j.2168-9830.2005.tb00869.x
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Indicators of Engineering Students' Success and Persistence

Abstract: Student success and persistence within the major and university were examined through hierarchical linear and logistic regression analyses for two cohorts of engineering students. Indicators of success and persistence were based on theoretical and empirical evidence and included both cognitive and noncognitive variables. Cognitive variables included high school rank, SAT scores, and university cumulative grade point average. Noncognitive factors included academic motivation and institutional integration. Outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
212
0
3

Year Published

2008
2008
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(236 citation statements)
references
References 19 publications
11
212
0
3
Order By: Relevance
“…Shuman, et al 35 showed that students on academic probation accounted for half the students who left engineering. Other research has shown a statistically significant difference in the GPA for students who remained in engineering versus those who left the university or switched to another major 36,37,38,39 . Hartman and Hartman 13 found significant difference in average GPA for males who left engineering and those who stayed, but there was no significant difference for females.…”
Section: Why Students Left Engineeringmentioning
confidence: 94%
“…Shuman, et al 35 showed that students on academic probation accounted for half the students who left engineering. Other research has shown a statistically significant difference in the GPA for students who remained in engineering versus those who left the university or switched to another major 36,37,38,39 . Hartman and Hartman 13 found significant difference in average GPA for males who left engineering and those who stayed, but there was no significant difference for females.…”
Section: Why Students Left Engineeringmentioning
confidence: 94%
“…Another venue of intense research is non-cognitive traits, which have borne mixed results. French et al 6 found no difference between students' motivation and institutional integration and cumulative GPA. On the other hand, Vogt 9 found a positive correlation between self-efficacy and engineering students' GPA.…”
Section: Academic Success In First Year Engineeringmentioning
confidence: 92%
“…In particular, previous academic achievement is frequently reported as a significant predictor of academic achievement 6 However, in some engineering schools, its predictive capacity is rather modest 7 . Therefore, other factors have been closely investigated.…”
Section: Academic Success In First Year Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, authors in one study found that interactions outside of ethnicity with faculty and peers were beneficial and increased underrerpresented students' confidence [22] . Overall, engineering students' interactions with faculty are vital for retention and persistence [23,24,25] and are especially critical for black and Latino students in ensuring their academic success [8,14,26,27] .…”
Section: Interactions With Facultymentioning
confidence: 99%